Nanofillers as a potential key for shaping the future of the industries - Venkteshwar Yadav; Dharm Pal; Anil Kumar Poonia (Hybrid Advances)
After the conceptualization of nanoparticles, various studies have been conducted, with nanofillers emerging as a significant focus. Nanofillers as a prominent research focus across multiple fields due to their diverse applications and unexplored properties within host matrixes. Moreover, there are several ideas for nanofiller synthesis and research gaps in the implementation of nanofillers in specific areas that need identification to enhance the overall performance of the developed composite materials. Understanding the behavior of nanofillers and host materials is crucial for this purpose. Additionally, based on morphological and dimensional perspectives, nanofillers are categorized and used for specific purposes in the host matrix. Despite the substantial advantages of nanofillers, certain limitations restrict their broader application across various industries. This review highlights key areas where nanofillers have been extensively applied, addressing associated challenges and proposing potential solutions. Additionally, the article examines the interaction mechanisms between nanofillers and host matrixes, providing innovative insights to emphasize emerging applications. Ultimately, the utilization of nanofillers offers significant potential to enhance material properties and tackle existing challenges across multiple sectors.